ANTESEDEN NIAT PERJALANAN DESTINASI ALAM DI BATAM - Wicipto, Wicipto; Hefri Ariyanto, Hepy (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
Batam City is well-known as a destination that frequently visited by visitors and a destination for domestic and foreign tourists. This is because Batam City has very diverse and beautiful tourist attractions. In the last 5 years, Batam City has experienced a very significant increase in the number of tourists. The factors that influence the number of visits are the destination image that Batam City has and a person's motivation to visit Batam City. The aim of this research is to determine the percentage level of influence between travel motivation and destination image on intentions to travel to nature destinations of Batam City. This research was conducted in Batam City using the Voluntary Response Sampling technique. The number of respondents was 283 respondents, namely domestic tourists. This research uses a descriptive verification method with a quantitative approach. The tool used in data analysis is SPSS version 26 software using simple linear regression. Based on the research results, it can be concluded that there is a significant positive influence between motivation and destination image on the intention to travel to natural tourism in Batam City, amounting to 49.8%. The higher the percentage of motivation and destination image, the higher a person's intention to travel to natural tourism in Batam City